Factors Related to Use KB Participants are Active in Understanding Contraceptive Devices (IUD) UPT Working Area DPPKB Bandar District, Simalungun Regency - Eka Sihombing; Yeci Theresia Simanjuntak (International Journal of Public Health Excellence (IJPHE), 2023)
Based on a preliminary survey conducted in the working area of UPT. DPPKB found that the use of Intrauterine Contraceptive Devices (IUD) was still small compared to other contraceptive methods. Meanwhile, IUD use has begun to be targeted every year. The purpose of this research is to find out what are the factors associated with IUD use. This type of research is quantitative research that is analytic in nature. This research was conducted in the working area of UPT. DPPKB Bandar District in August 2017. The population in this study amounted to 10,429 people with a sample of 189 people. The instrument used was a questionnaire using the Chi-sguare test and SPSS program assistance. Based on the results of the study it was found that the total number of family planning participants had low education, namely 123 people (65.1 % ). The majority of respondents with low education did not use the IUD as many as 118 people (95.9 % ) while only $ people (4.1%) used it. There is a relationship between education and IUD use (P=0.000<0.05 ). Family planning participants had low knowledge, namely 123 people (65.1 % ). The majority of respondents with low knowledge did not use the IUD as many as 121 people (98.4 % ) while only 2 people (1.6%) used it. There is a relationship between knowledge and use of the IUD (P=0.000<0.05 ) . Family planning participants who did not receive support from their husbands were 175 people (92.6 % ). The majority of respondents who did not receive support from their husbands did not use the IUD as many as 164 people ( 93.7 %) while only 1 person (6.3%) used it. There is a relationship between husband's support and IUD use (P=0.000<0.05 ).